Utilization of Bagasse as a Substitute for Coal Fuel in Steam Boilers - Muhammad Brilliant Bidjaksono; Ahyahudin Sodri; Dony Abdul Chalid (Jurnal Penelitian Pendidikan IPA, 2024)
Biomass utilization is believed to bring environmental and socio-economic benefits—PT X coal in a steam boiler. The research method used is a mix of quantitative and qualitative. The concentration of particulates that coal produces is higher than that of sugar cane bagasse. The NOx parameter values produced by bagasse and coal showed insignificant results. Meanwhile, coal boilers with higher temperatures produced higher NOx than NOx from biomass. The distribution concentration of SOx in bagasse biomass is higher than coal SOx emissions. A total of 26 communities agreed to change the use of coal to bagasse biomass. Utilization of bagasse biomass provides income of up to 94,000,000,000. Using bagasse as steam boiler fuel has a more positive impact than coal.